THE INTRAUTERINE DEVICE (IUD) USE AND BACTERIAL VAGINOSIS INCIDENCE, INSIGHTS FORM 2023 STUDY IN A SURABAYA, INDONESIA - Biutifasari, Verna; Eka Fitriani Hafel; Prasetyadi , Frans O.H.; Adiwinoto, Ronald Pratama; Hardjono, Ellen Angelique (UNIVERSITAS AIRLANGGA, 2025)
Background: The Intrauterine device (IUD) is one of the most widely used and effective long-term contraceptive methods, with a success rate exceeding 99%. However, prolonged copper IUD use has been associated with an increased risk of bacterial vaginosis (BV), with users reportedly 1.28 times more likely to develop BV than users of other contraceptive methods.This study aims to assess the association between IUD usage and the incidence of BV. Methods: This cross-sectional analytic observational study included 50 participants using IUDs, recruited from three public health centers in Surabaya between May and December 2023. Vaginal swab samples from suspected BV cases were examined independently by two observers. Data were analyzed using the Chi-square test to assess associations and Cronbach's Alpha to evaluate inter-observer reliability, with significance set at p < 0.05. Results: Most BV cases were found among women aged 30–39 years (40%) and among users of non-hormonal IUDs (76%). Based on Nugent scoring, 26 participants (52%) were diagnosed with definitive BV. The association between IUD use and BV incidence was not statistically significant (p = 0.090). Inter-observer reliability was high, with a Cronbach’s Alpha of 0.963. Conclusion: The study concludes that IUD use is not significantly associated with the occurrence of bacterial vaginosis, based on Nugent score evaluation.